Soil-Blade Interaction of a Rotary Tiller: Soil Bin Evaluation - Mandal, Subrata Kr; Bhattacharyya, Basudeb; Mukherjee, Somenath; Karmakar, S (International Journal of Sustainable Agricultural Research, 2014)
In this paper soil-blade investigation of a rotary tiller in a controlled soil bin is presented. Among the soil cutting agricultural tools currently used, the rotary tiller is one of the most promising equipment, saving operating time and labor. In a rotary tiller working tool is always a blade. For the tillage systems, accurately predicting the required torque and penetration force while cutting of soil with a blade is of prime importance as far as the farming operation is concerned. In the tillage operation almost 50% of total farm power is utilized. Draft require for tillage depend on the soil strength and moisture contents along with compactness. So tillage should be done at such a moisture content and soil strength where minimum power will be consumed. This moisture content and soil strength is the optimized value. It is needed to evaluate optimum values of these two important parameters for every type of soil before tillage operation to decrease the loss of power. Thus in this paper an investigation with regards to moisture content and soil strength which affects penetration resistance force and toque while soil cutting through a rotary tiller blade and has been presented.